2022
DOI: 10.7554/elife.76063
|View full text |Cite
|
Sign up to set email alerts
|

scRNA-sequencing reveals subtype-specific transcriptomic perturbations in DRG neurons of PirtEGFPf mice in neuropathic pain condition

Abstract: Functionally distinct subtypes/clusters of dorsal root ganglion (DRG) neurons may play different roles in nerve regeneration and pain. However, details about their transcriptomic changes under neuropathic pain conditions remain unclear. Chronic constriction injury (CCI) of the sciatic nerve represents a well-established model of neuropathic pain, and we conducted single-cell RNA-sequencing (scRNA-seq) to characterize subtype-specific perturbations of transcriptomes in lumbar DRG neurons on day 7 post-CCI. By u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…The component heterogeneity of somatosensory neurons in the DRG is essential to relay different peripheral inputs to the central nervous system ( Abraira and Ginty, 2013 ; Gatto et al, 2019 ; Li et al, 2016 ; Todd, 2010 ). The heterogeneity in the molecular transcriptomes, neuronal types, and functional properties of DRG neurons in rodents has been well characterized ( Hu et al, 2016 ; Li et al, 2016 ; Renthal et al, 2020 ; Usoskin et al, 2015 ; Wang et al, 2021a ; Zhang et al, 2022 ; Zhou et al, 2022 ). Recently, emerging evidence has revealed the organization of human DRG somatosensory neurons ( Jung et al, 2023 ; Nguyen et al, 2021 ; Tavares-Ferreira et al, 2022 ; Yu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The component heterogeneity of somatosensory neurons in the DRG is essential to relay different peripheral inputs to the central nervous system ( Abraira and Ginty, 2013 ; Gatto et al, 2019 ; Li et al, 2016 ; Todd, 2010 ). The heterogeneity in the molecular transcriptomes, neuronal types, and functional properties of DRG neurons in rodents has been well characterized ( Hu et al, 2016 ; Li et al, 2016 ; Renthal et al, 2020 ; Usoskin et al, 2015 ; Wang et al, 2021a ; Zhang et al, 2022 ; Zhou et al, 2022 ). Recently, emerging evidence has revealed the organization of human DRG somatosensory neurons ( Jung et al, 2023 ; Nguyen et al, 2021 ; Tavares-Ferreira et al, 2022 ; Yu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent advance in single-cell RNA sequencing (scRNA-seq) allows the characterization of transcriptomic changes across different functionally distinct cell types down to single-cell resolution in DRGs. Recently, scRNA-seq revealed heterogenous, subtype-specific transcriptomic changes in DRGs ( Hu et al, 2016 ; Zhang C. et al, 2022 ) and retinal ganglion cells ( Jacobi et al, 2022 ; Li et al, 2022 ) after axotomy. The distinct gene expression changes in different neuronal subtypes might account for the differences in the intrinsic growth capacity of different neuronal subtypes.…”
Section: Future Perspective: Targeting the Right Source For Improved ...mentioning
confidence: 99%
“…(F) Neuronal subtypes of mouse DRG from the study of Zhou et al (2022) . (G) Neuronal subtypes of rat DRG by Zhang et al (2022) . NF, neurofilament; PEP, peptidergic; NP, non-peptidergic; TH, tyrosine hydroxylase; MHN, mechanoheat nociceptor; MI, mechanically insensitive; IS, itch-sensitive; MS, mechanically sensitive; MN, mechanical nociceptor; MR, mechanoreceptor; C-LTMR, C-fiber low-threshold MR; SST, somatostatin.…”
Section: Mouse Neuronal Typesmentioning
confidence: 99%
“…Although increasing number of studies have attempted to classify DRG neurons at single-cell resolution, the heterogeneity in sequencing methods, laboratory protocols, or sample treatments between studies led to some divergent results. In general, DRG neurons across species were classified into PEPs and NPs ( Usoskin et al, 2015 ; Hu et al, 2016 ; Renthal et al, 2020 ; Kupari et al, 2021 ; Wang et al, 2021 ; Zhang et al, 2022 ; Zhou et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ), NFs ( Usoskin et al, 2015 ; Renthal et al, 2020 ; Zhang et al, 2022 ), and C-LTMRs ( Usoskin et al, 2015 ; Hu et al, 2016 ; Li et al, 2016 ; Renthal et al, 2020 ; Kupari et al, 2021 ; Tavares-Ferreira et al, 2022 ; Zhou et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ) in most included studies of this review. Other common neuronal subtypes, such as TRPM8 ( Kupari et al, 2021 ; Zhou et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ), SST ( Renthal et al, 2020 ; Zhou et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ), proprioceptors ( Usoskin et al, 2015 ; Hu et al, 2016 ; Tavares-Ferreira et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ), Aβ-LTMR ( Renthal et al, 2020 ; Tavares-Ferreira et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ), Aδ-LTMR ( Tavares-Ferreira et al, 2022 ; Jung et al, 2023 ; Yu et al, 2023 ) were commonly identified in several studies.…”
Section: Similarities or Differences Between Different Studies In Ter...mentioning
confidence: 99%